2001
DOI: 10.1080/026404101750158358
|View full text |Cite
|
Sign up to set email alerts
|

Stability of psychometric questionnaires

Abstract: In 1999, Wilson and Batterham proposed a new approach to assessing the test-retest stability of psychometric questionnaires. They recommended assessing the proportion of agreement - that is, the proportion of participants that record the same response to an item - using a test-retest design. They went on to use a bootstrapping technique to estimate the uncertainty of the proportion of agreement. The aims of this short communication are (1) to demonstrate that the sampling distribution of the proportion of agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 16 publications
0
82
0
3
Order By: Relevance
“…Differences in response to each domain on the COMI were ±1 category in 98% patients for the domain 'function', 96% for 'symptom-specific well-being', 97% for 'general quality of life', 99% for 'social disability' and 100% for 'work disability', hence all satisfying the stability criterion of C90% suggested by Nevill et al [22]. Table 3 shows the mean (SD) scores on the two test occasions, and the ICC, SEM and MDC95% for each of the scales.…”
Section: Reproducibilitymentioning
confidence: 95%
See 2 more Smart Citations
“…Differences in response to each domain on the COMI were ±1 category in 98% patients for the domain 'function', 96% for 'symptom-specific well-being', 97% for 'general quality of life', 99% for 'social disability' and 100% for 'work disability', hence all satisfying the stability criterion of C90% suggested by Nevill et al [22]. Table 3 shows the mean (SD) scores on the two test occasions, and the ICC, SEM and MDC95% for each of the scales.…”
Section: Reproducibilitymentioning
confidence: 95%
“…For the COMI fivepoint ordinal scales, reproducibility (stability) of measures was assessed by examining the proportion of participants recording test-retest differences for each item within a reference value of ±1 point (where at least 90% was considered acceptable) [22,26]. For scales/items with approximately normally distributed interval data (pain scales, COMI summary score, Roland Morris, ODI), oneway repeated measures ANOVA was used to assess the differences in means for the repeated trials and to determine the intraclass correlation coefficient (ICC; model ICC agreement 2,1 ) and their 95% confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a strategy may be premature until the stability of the TOPS factor structure is established. Unless it can be demonstrated that scores on a questionnaire are stable under conditions where no change is expected, any changes observed may be caused by random error potentially associated with participants not understanding the meaning of items (see Nevill et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A voluntary informed consent of the beginning climbers' parents was signed previously. The instrument was applied at two different moments with one week of difference (Baumgartner, 2000;Nevil, et al 2001). As usually, the instrument was tested in the same conditions on an indoor climbing wall.…”
Section: Methodsmentioning
confidence: 99%